Variational Approach Applied to Study the Lifting of a Non-Newtonian Fluid on a Vertically Moving Belt - FAROOQ, Ali Ahmad; SIDDIQUI, Abdul Majeed; HAROON, Tahira; RANA, Muhammad Afzal (Walailak Journal of Science and Technology (WJST), 2014)
This paper provides an investigation regarding the modeling and analysis of the thin film flow of a non-Newtonian Williamson fluid on a vertically moving belt. The governing nonlinear differential equation is first integrated analytically and then solved by using the Variational Iteration Method (VIM). The results of the present method are also compared with those obtained by the Adomian Decomposition Method (ADM) and a very good agreement is observed. This comparison reveals that VIM may be considered as an efficient alternative method for solving nonlinear problems arising in the area of fluid mechanics. Expressions for some important physical quantities such as volume flux, average velocity, the belt speed for the lifting of non-Newtonian fluid are also derived. doi:10.14456/WJST.2014.74